2017
DOI: 10.1007/s00253-017-8143-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of threshing and redrying on bacterial communities that inhabit the surface of tobacco leaves

Abstract: Before being subjected to the aging process, raw tobacco leaves (TLs) must be threshed and redried. We propose that threshing and redrying affect the bacterial communities that inhabit the TL surface, thereby influencing the aging process. However, these effects remain unclear. In this study, Illumina sequencing was applied to analyze the bacterial communities on both raw and redried TLs. Shannon's diversity value decreased from 3.38 to 2.52 after the threshing and redrying processes, indicating a large reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Genomic DNA was extracted based on previous studies (Su et al, 2011 ; Ye et al, 2017 ; Zhang, Acuña, et al, 2019 ). For each biological replicate, 60 g of CTLs was ground with liquid nitrogen and then divided into three equal parts, namely the technical replicates; then, the DNA extracted from the three technical replicates of each sample was pooled into one DNA sample to minimize any potential DNA extraction bias.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genomic DNA was extracted based on previous studies (Su et al, 2011 ; Ye et al, 2017 ; Zhang, Acuña, et al, 2019 ). For each biological replicate, 60 g of CTLs was ground with liquid nitrogen and then divided into three equal parts, namely the technical replicates; then, the DNA extracted from the three technical replicates of each sample was pooled into one DNA sample to minimize any potential DNA extraction bias.…”
Section: Methodsmentioning
confidence: 99%
“…The fungal internal transcribed spacer gene was amplified using the universal primers ITS1F (5ʹ‐CTTGGTCATTTAGAGGAAGTAA‐3ʹ) and ITS2R (5ʹ‐GCTGCGTTCTTCATCGATGC‐3ʹ). The PCR system and program were chosen based on a previous study (Ye et al, 2017 ). The PCR products were extracted and purified using an AxyPrep DNA Gel Extraction Kit (Axygen Biosciences, Union City, CA, USA) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco (Nicotiana tabacum L.) is a special industrial crop planted in over 120 countries and regions (Ye et al, 2017). Most of fresh tobacco is made into ue-cured tobacco (FCT).…”
Section: Introductionmentioning
confidence: 99%
“…The aging process usually takes 1 to 2 years, which is long along with low e ciency. It is necessary to seek approaches to enhance sensory the aging e ciency (Ye et al 2017;. Previous studies has reported that some speci c functional microorganisms were high effective in improving the quality (Chortyk O. T. et al 1973;He 2013;Li et al 2019) or degrading nicotine of FCT (He et al 2019) in aging process.…”
Section: Introductionmentioning
confidence: 99%